THU0112 Myeloid-Derived Suppressor Cells have Regulatory Roles in Mouse Collagen-Induced Arthritis. (23rd January 2014) - Fujii, W.; Ashihara, E.; Hirai, H.; Nagahara, H.; Fujioka, K.; Murakami, K.; Seno, T.; Yamamoto, A.; Ishino, H.; Kohno, M.; Maekawa, T.; Kawahito, Y.
Abstract : Background: Myeloid-derived suppressor cells (MDSCs) are of myeloid origin and are able to suppress T cell responses. MDSCs are characterized by the co-expression of the myeloid differentiation antigens Gr-1 and CD11b in mice (1 ). MDSCs in cancer have been studied in detail and are known to play roles in tumor associated immune suppression. However, the roles of MDSCs in autoimmune disease remain controversial and little is known about MDSCs in autoimmune arthritis. Objectives: We investigate the roles of MDSCs in autoimmune arthritis using collagen-induced arthritis (CIA) mouse models. Methods: We determined the number of Gr-1 + CD11b + MDSCs in the spleens of CIA mice by flow cytometry. Next, we isolated MDSCs from CIA mice by magnetic cell sorting and cultured with CD4 + T cells to analyze the functions of MDSCs. We investigated the proliferation of CD4 + T cells by CFSE dye dilution assay and estimated cytokine levels produced by CD4 + T cells using ELISA. Furthermore, we investigated CD4 + T cell differentiation into Th17 cells by flow cytometry. Finally, we performed adoptive transfer of MDSCs into CIA mice and investigated the severity of arthritis. Results: MDSCs significantly accumulated in the spleens of mice with CIA when arthritis severity peaked. These MDSCs inhibited CD4 + T cell proliferation and differentiation into Th17 cells. Moreover, MDSCs inhibited the production of IFNγ, IL-2, TNFα, and IL-6 by CD4 + T cells in vitro, whereas they promoted the production of IL-10. Adoptive transfer of MDSCs reduced both clinical (Image A) and histological arthritis scores (Image B) in vivo, which was accompanied by a decrease in the number of CD4 + T cells and Th17 cells in the draining lymph nodes. Image/graph: Conclusions: MDSCs in CIA suppress the progression of CIA by inhibiting the pro-inflammatory immune response of CD4 + T cells. These observations suggest that MDSCs play crucial roles in the regulation of autoimmune arthritis, which could be exploited in new cell-based therapies for human rheumatoid arthritis (RA). References: Gabrilovich, D. I., and S. Nagaraj. 2009. Myeloid-derived suppressor cells as regulators of the immune system. Nat. Rev. Immunol. 9: 162-174. Disclosure of Interest: None Declared